Knowledge, attitude, and practice study among healthcare workers, during COVID-19 pandemic in an aspiring district of Uttar Pradesh - Yadav, Richa; Pandey, Omprakash; Shukla, Rajendra K.; Yadav, Geeta (International Journal of Research in Medical Sciences, 2020)
Background: COVID-19 (coronavirus disease 2019) declared pandemic by WHO on 30th January 2020. Till date there is no antiviral treatment or vaccine has been developed for COVID-19. Primary preventive measures include regular hand washing, social distancing and respiratory etiquettes are only proven methods till date. Methods: A type of questionnaire based cross sectional study was conducted among the healthcare workers (HCWs) of Maharaja Suheldev Autonomous State Medical College, Bahraich. Results: In this predominantly uneducated and socially backward area, majority of participants had knowledge about COVID-19 precautionary measures and most of them are confident of winning over the disease; 77.5% were confident of successfully controlling the disease, yet maximum healthcare workers took seriously the precautionary measures. Conclusions: Good COVID-19 knowledge is associated with optimistic attitudes and appropriate practices towards COVID-19, suggesting that health education programs aimed at improving COVID-19 knowledge are helpful for encouraging an optimistic attitude and maintaining safe practices.